ANALISIS RISIKO PADA SUPPLY CHAIN MANAGEMENT MENGGUNAKAN FRAMEWORK ISO 31000:2009 (STUDI KASUS: PT. XYZ) - Asri Sahraen; Alfan Andri; Susanti Sundari (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
The current supply chain is very much less vulnerable to uncertainty and risks that can disrupt the supply chain which can lead to losses in the form of income, competitive advantage and profits if not managed effectively. Supply chain risk management is the management of supply chains through coordination or collaboration between supply chain partners to ensure profitability and continuity. PT. XYZ is a company that focuses on printer and parts distributors. PT.XYZ's activities which are always in touch with suppliers, consumers and management between the center and branches have various kinds of risks, which can cause the company not to achieve the desired target. This study aims to identify supply chain risks at PT. XYZ using the ISO 31000: 2009 framework and how mitigation solutions are carried out to reduce existing risks. The results of this study indicate that 20 risk indications have been evaluated. The identification is classified into 7 risk categories, namely operational, supply, demand, information, policy, product and finance. Based on the risk analysis, it is known that the risk occurs in operations. Operational risk is related to the ability of employees to offer products and has an impact on the level of company revenue and the lack of a procurement workforce resulting in difficulties in fulfilling the demand for each branch.